Country of origin branding: an integrative perspective. Issue 4 (18th July 2016) - Brodie, Roderick J.; Benson-Rea, Maureen
Abstract : Purpose: A new conceptualization of the process of country of origin (COO) branding based on fresh theoretical foundations is developed. This paper aims to provide a strategic perspective that integrates extant views of COO branding, based on identity and image, with a relational perspective based on a process approach to developing collective brand meaning. Design/methodology/approach: A systematic review of the literature on COO branding and geographical indicators is undertaken, together with a review of contemporary research on branding. Our framework conceptualizes COO branding as an integrating process that aligns a network of relationships to co-create collective meaning for the brand's value propositions. Findings: An illustrative case study provides empirical evidence to support the new theoretical framework. Research limitations/implications: Issues for further research include exploring and refining the theoretical framework in other research contexts and investigating broader issues about how COO branding influences self and collective interests in business relationships and industry networks. Practical implications: Adopting a broadened perspective of COO branding enables managers to understand how identity and image are integrated with their business relationships in the context of developing collective brand meaning. Providing a sustained strategic advantage for all network actors, an integrated COO branding process extends beyond developing a distinctive identity and image. Originality/value: Accepted consumer, product, firm and place level perspectives of COO branding are challenged by developing and verifying a new integrated conceptualization of branding.